2018
DOI: 10.1038/s41467-018-06186-1
|View full text |Cite
|
Sign up to set email alerts
|

A bidentate Polycomb Repressive-Deubiquitinase complex is required for efficient activity on nucleosomes

Abstract: Attachment of ubiquitin to lysine 119 of Histone 2A (H2AK119Ub) is an epigenetic mark characteristic of repressed developmental genes, which is removed by the Polycomb Repressive-Deubiquitinase (PR-DUB) complex. Here we report the crystal structure of the Drosophila PR-DUB, revealing that the deubiquitinase Calypso and its activating partner ASX form a 2:2 complex. The bidentate Calypso–ASX complex is generated by dimerisation of two activated Calypso proteins through their coiled-coil regions. Disrupting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 69 publications
0
53
0
Order By: Relevance
“…During the revision of this manuscript, Foglizzo et al (2018) reported the crystal structure of a DmPR-DUB complex that closely resembles our complex. Based on their analyses the authors suggest a 2:2 complex where two Calypso/ASX heterodimers dimerize via the Calypso coiled-coil regions.…”
Section: Discussionmentioning
confidence: 74%
“…During the revision of this manuscript, Foglizzo et al (2018) reported the crystal structure of a DmPR-DUB complex that closely resembles our complex. Based on their analyses the authors suggest a 2:2 complex where two Calypso/ASX heterodimers dimerize via the Calypso coiled-coil regions.…”
Section: Discussionmentioning
confidence: 74%
“…The stoichiometry of Calypso/Asx was 1:1 molar ratio in low protein concentration, and 2:2 molar ratio in high protein concentration (21). Crystal structure work on the deubiquitinase Calypso, the Drosophila counterpart of BAP1, and its activating deubiquitinase adaptor (Deubad) protein partner ASX have provided a structural basis to interpret studies demonstrating that the ASXL1/2 Deubad domains bind tightly to BAP1, and thereby activate the PR-DUB complex by forming a composite binding site for ubiquitin (21). As in our study, Foglizzo et al (21) showed that mutations at the juncture between DUB, Deubad, and ubiquitin have a deleterious effect on the ability of the PR-DUB to interact with ubiquitin.…”
Section: Discussionmentioning
confidence: 99%
“…Association of the ULD and DEUBAD domains increases the affinity of the PR-DUB for ubiquitin and is required for deubiquitination [ 6 , 9 , 10 ]. At the C-terminus of their ULD domains, Calypso and BAP1 each have positively charged C-terminal extensions, which are required for binding the net negatively charged nucleosome [ 8 , 9 ]. A major difference in domain architecture between BAP1 and Calypso is an insertion of around 380 amino acids into the ULD domain of BAP1, which is proposed to enable a broader range of interactions by the mammalian protein [ 11 , 12 , 13 ] ( Figure 1 ).…”
Section: Pr-dub the Polycomb-repressive Deubiquitinasementioning
confidence: 99%
“…Two near-identical structures of Calypso bound to the DEUBAD of Asx were recently solved and provide structural insight into deubiquitination by the PR-DUB [ 8 , 23 ]. In these structures, the UCH domain of Calypso is linked to the ULD through a coiled-coil hairpin.…”
Section: Regulation Of Pr-dub Catalytic Activitymentioning
confidence: 99%